Evolving insights on the role of microglia in neuroinflammation, plasticity, and regeneration of the injured spinal cord - Swarts, Emily A.; Brennan, Faith H. (Frontiers in Immunology, 2025)
Microglia have emerged as central players in the pathophysiology of traumatic spinal cord injury (SCI). The purpose of this brief review is to highlight the evolution of knowledge on the role of microglia in SCI. We explore the initial discovery of macrophages and their role in SCI lesions, followed by how microglia were examined and distinguished from monocyte-derived macrophages. We then discuss findings from studies that mapped and manipulated microglia in experimental SCI, made possible through technological advances in genetic, pharmacological, and bioinformatic approaches. We also highlight the importance of considering how the timing and location of microglia activation shapes neuroinflammation, synaptic plasticity and intraspinal circuit remodelling. Finally, as microglia research continues to flourish, we consider how microglia could be harnessed therapeutically to promote repair and functional recovery of motor, sensory, and autonomic systems after SCI.